Prioritizing Pregnant Women for Coronavirus Disease 2019 Vaccination in African Countries . (8th June 2022) - Nachega, Jean B; Sam-Agudu, Nadia A; Siedner, Mark J; Rosenthal, Philip J; Mellors, John W; Zumla, Alimuddin; Hermans, Michel P; Ntakwinja, Mukanire B; Mukwege, Denis M; Langenegger, Eduard; Mofenson, Lynne M
Abstract: Coronavirus disease 2019 (COVID-19) in pregnancy is associated with excess maternal and infant morbidity and mortality in both African and higher-resource settings. Furthermore, mounting evidence demonstrates the safety and efficacy of COVID-19 vaccination for pregnant women and infants. However, national guidelines in many African countries are equivocal or lack recommendations on COVID-19 vaccine in pregnancy. We summarize key data on COVID-19 epidemiology and vaccination among pregnant African women to highlight major barriers to vaccination and recommend 4 interventions. First, policymakers should prioritize pregnant women for COVID-19 vaccination, with a target of 100% coverage. Second, empirically supported public health campaigns should be sustainably implemented to inform and support pregnant women and their healthcare providers in overcoming vaccine hesitancy. Third, COVID-19 vaccination for pregnant women should be expanded to include antenatal care, obstetrics/gynecology, and targeted mass vaccination campaigns. Fourth, national monitoring and evaluation of COVID-19 vaccine uptake, safety, surveillance, and prospective outcomes assessment should be conducted. Abstract : Evidence from African and non-African settings indicates that coronavirus disease 2019 (COVID-19) in pregnancy is associated with excess maternal and infant morbidity and mortality. We recommend universal COVID-19 vaccination for pregnant African women, as available data on safety and efficacy in pregnancy are reassuring.